Yoon Suk Yeol’s policy towards Japan: Reasons for changing approach and prospects - К. V. Asmolov; О. S. Pugacheva (Японские исследования)
In May 2022, Yoon Suk Yeol, representing conservative political forces, became the President of the Republic of Korea (ROK, South Korea). He advocated the speedy normalization of relations with Japan, giving priority to pragmatic cooperation between the two countries. The conservative ruling circles in South Korea are focused on developing and deepening cooperation with the countries of the collective West, including Japan, which share the values of liberal democracy. President Yoon considers Japan a “partner” with whom it is possible to counter common threats, in particular North Korea (Democratic People’s Republic of Korea, DPRK). His administration aims at the extended deterrence of its northern neighbor, the implementation of which recognizes the role of Japan within the trilateral format of cooperation between the ROK, the United States, and Japan. On the other hand, Yoon’s administration emphasizes its intention to develop future-oriented relations with Tokyo, expressing its readiness not to raise controversial issues of the historical past. However, the issue of assessing the colonial past of the ROK as well as ones of building relations with Japan are an extremely sensitive matter in South Korean domestic political life. In this regard, it is relevant to trace the influence of domestic politics on the ROK’s course towards Japan. The article shows that Yoon Suk Yeol’s Japanese policy is part of the internal struggle for the formation of historical memory, while the opposition of conservative forces to the discourse of progressives also serves the purpose of legitimizing the political course of the current administration towards Japan. According to the authors, the propaganda-historical narrative of President Yoon indicates an attempt to move away from anti- Japanese sentiment as a key element of the South Korean ideology. The authors examine the key characteristics of the Japanese discourse of President Yoon Suk Yeol, as well as the reasons that determined his policy of normalizing and strengthening relations with Tokyo. In conclusion, assessments are presented regarding the prospects for Yoon’s pro-Japanese course and relations between Seoul and Tokyo, including in light of the results of the parliamentary elections that took place in the ROK on April 10, 2024.